(untitled) (Annals of Medical Research, 2021)
Aim: Comparison of clinical efficacy and safety of trabeculectomy and deep sclerectomy with mitomycin-C (MMC) surgeries.Material and Methods: 58 eyes of 58 patients with glaucoma who underwent trabeculectomy or deep sclerectomy with MMC were evaluated retrospectively. The success criterion was regarded as follows; patients having intraocular pressure (IOP) less than 21 mmHg was regarded as complete success; patients with IOP less than 21 mmHg with medication was regarded as partial success; and patients with IOP higher than 21 mmHg with medication was regarded as un-success.Results: There was no statistically significant difference in IOP lowering effects between the two surgeries. Considering the success of the groups; complete success was achieved in 32 patients (91.4%) and partial success in 3 patients (8.6%) in the trabeculectomy group. Complete success was achieved in 20 patients (86.9%) and partial success in 3 patients (13.1%) in the deep sclerectomy with MMC group. In the deep sclerectomy with MMC group, hypotonia was detected in 2 patients (8.7%). In the trabeculectomy group, 5 patients (14.3%) had hypotonia, 2 patients (5.7%) had shallow anterior chamber and 1 patient (2.85%) had choroidal detachment.Conclusion: When IOP lowering effects of deep sclerectomy with MMC and trabeculectomy operations were compared, it was found that there was no statistically significant difference between the two techniques. When complication rates were compared, less complication was found in deep sclerectomy operations. It can be concluded that deep sclerectomy is safer than trabeculectomy and as effective as it is. Keywords: Deep Sclerectomy; Glaucoma; Trabeculectomy.